Effect of Sulfhydryl Reagents on the Ribosomes of Bacillus subtilis - Ranu, Rajinder Singh (1971)
The effect of various sulfhydryl reagents on the ribosomes of Bacillus subtilis was studied. The 70S ribosomes were completely dissociated into 30S and 50S subunits by appropriate concentrations of p-chloromercuribenzoic acid (PCMB) and 5,5′-dithio-bis-(2-nitro-benzoic acid). The N-ethylmaleimide and iodoacetamide failed to dissociate the ribosomes even at relatively high concentrations. The rate of dissociation of ribosomes by PCMB varied with the concentration of ribosomes. A progressive decrease in the rate of dissociation was observed as the concentration of ribosomes in the reaction mixture was increased. The PCMB-induced ribosomal subunits were unable to reassociate into 70S monomers unless they were dialyzed against buffer containing β-mercaptoethanol. On the average, four molecules of PCMB per 70S ribosome and two molecules of PCMB per each 30S and 50S subunit were bound. The number of PCMB molecules bound per ribosome did not change with increasing concentrations of PCMB, even though higher concentrations of PCMB resulted in dissociation of ribosomes into subunits.